Frequency of Entamoeba Complex in Individuals Referred to the Medical Laboratories in Jahrom City, South of Iran - Zahra Kargar Jahromi; Ali Taghipour; Kavous Solhjoo; Rahim Raoufi (Journal of Parasitology Research)
This study aimed to determine the prevalence of Entamoeba histolytica, Entamoeba dispar, and Entamoeba moshkovskii, using microscopic and molecular methods in Jahrom city (Fars Province), south of Iran. Stool samples were collected from 360 outpatients referred to the medical laboratories in Jahrom city. Standard parasitological methods, including direct wet mount examination, formalin–ether sedimentation technique, and trichrome staining techniques, were used for detection of Entamoeba complex. Nested polymerase chain reaction (PCR) was used to identify the genus/species of Entamoeba. Entamoeba complex cysts were detected in 2.5% (9/360) of samples by microscopic methods, while 11 isolates were considered positive for the Entamoeba complex by nested PCR. Among them, 2 (18.18%) out of 11 samples were E. histolytica, 5 (45.45%) were E. dispar, and 4 (36.36%) were E. moshkovskii. Molecular positivity was more prevalent among females (4.16%), people living in rural areas (3.44%), and people over 60 years old (13.33%). Considering the clinical manifestations, the Entamoeba complex infection in patients with fever (7.69%), severe diarrhea (5.10%), and nausea (5%) was high. This study reported the presence of E. histolytica, E. dispar, and E. moshkovskii in Jahrom city. Therefore, we suggest more public health interventions in Jahrom city.